Primary Plasma Cell Leukaemia with Lambda Light Chain secretion and Chromosomal abnormalities presenting as hyperleukocytosis - A case report. (Bangladesh Journal of Medical Science, 2023)
Primary plasma cell leukaemia (pPCL) is a rare and lethal form of plasma cell dyscrasia that can occur either de novo (primary) or as a leukemic transformation of refractory or relapsed multiple myeloma. We report a case of pPCL with lambda light chain disease and multiple chromosomal abnormalities in a 75-year-old female who presented with generalized weakness. Her peripheral blood smear showed hyperleukocytosis with 78% circulating plasma cells. Serum protein electrophoresis (SPE) does not reveal the M band and serum immunofixation (SI) light chain analysis in serum showed an elevated lambda light chain. Skeletal radiography and PET-CT (positron emission tomography—computerized tomography) did not reveal any lytic lesions. Immunophenotypic studies reveal a CD38-positive population with negativity for T cells, B cells, myeloid markers, and a negative CD45. Fluorescent in situ hybridization (FISH) analysis results disclosed the deletion of 13q14.3 and t(11; 14). This case highlighted the usefulness of the peripheral smear findings and high fluorescent lymphocyte activity, which directed the pathologist to initiate workup for pPCL, and comprehensive laboratory biochemical and radiological evaluation further helps to confirm and differentiate pPCL from multiple myeloma.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 932-936